Optimasi Parameter Proses di Mesin 3D Printing Jenis Fused Deposition Modeling (FDM) dengan Filamen ABS pada Produk Poros Berpasangan menggunakan Metode Taguchi - Purnawarman, Otto (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2023)
Making customizing single product, we can use the additive manufacturing method. One of the additive manufacturing technologies is 3D printing. 3D Printing machines which often found on the market are Fused Depsition Modeling (FDM) technology. The fused deposition method or FDM is an additive manufacturing method which uses the concept of adding layers or materials to each layer. One of the main materials in the 3D printing process is ABS filament. However, the 3D Printing machine with FDM technology has a weakness, if you want to make products that are paired and have tolerances it will be difficult because the surface will appear to have lines that show the boundaries between layers. These lines are influenced by the parameters contained in 3D Printing. The Taguchi method is used to obtain optimum parameter variations and uses ANOVA analysis to determine what factors influence the shrinkage response to specific tolerances. The optimum combination of parameters on the shrinkage/deviation response to special tolerances on the inside diameter, namely nozzle temperature 230, print speed 70 and layer height 0.20. And on the outside diameter, namely the nozzle temperature is 250, the print speed is 90 and the layer height is 0.2.